Effect of coastal boundary representation on basin-scale internal waves. Issue 2 (3rd April 2021) - Ito, Wataru; Nakayama, Keisuke; Shintani, Tetsuya
ABSTRACT: In numerical simulations for large-scale coastal environments, it is crucial to accurately reproduce internal Kelvin and Poincare waves under Coriolis forcing. Therefore, for surface waves, the effects of horizontal grid representation on Kelvin and Poincare waves have been investigated using both structured and unstructured grid models. However, the effect of the grid representation on internal waves is poorly understood so far, especially for structured grids which uses a step-like lateral boundary. This study thus investigates the applicability of structured grids into internal Kelvin and Poincare waves using a circular basin to exclude the effect of open boundaries and discusses numerical errors in terms of the Rosbby-grid factor. Several grid sizes were used for a structured grid simulation, which demonstrated that the structured grid simulation reproduced the internal Kelvin and Poincare waves sufficiently accurately compared to those obtained by the unstructured grid simulation. Furthermore, the structured grid simulation was also confirmed to agree very well with the unstructured grid simulation in a conical basin which exhibits more realistic geometry. It was thereby shown the possibility that internal waves can be accurately analyzed using structured grids when the Rossby-grid factor is more than 10.